CONCEPTUAL RECONSTRUCTION OF MEDICAL CONSENT IN HEALTHCARE SERVICES: Islamic Contract Law Analysis of the Principle of At-Tarāḍī - Naimah Naimah; Gunnarto Gunnarto; Anis Mashdurohatun; Atta Abdel Aaty El-Sonbaty; Anies Marsudiati Purbadiri (Fakultas Syariah, 2026)
Medical consent (informed consent) is a fundamental mechanism in ensuring patient autonomy and legal protection in healthcare services. Although comprehensively regulated in Indonesian health law, the practice of informed consent still tends to be procedural and administrative in nature, thus failing to fully guarantee the patient's substantive willingness and understanding. This condition reveals a structural imbalance in the doctor-patient relationship that has the potential to weaken the legal position of patients. This study aims to analyse the conceptual weaknesses of informed consent in Indonesian positive law and reconstruct it through the integration of the principle of at-tarāḍī in Islamic contract law. The research method used is normative legal research with a conceptual, doctrinal, and comparative normative approach, through analysis of health legislation, legal doctrine, and fiqh muʿāmalāt principles. The results of the study indicate that the regulation of informed consent in national regulations emphasises the fulfilment of formalities of consent rather than the substantial quality of the patient's willingness and free will. By reconceptualising informed consent as a medical service contract based on the principle of at-tarāḍī, this study offers a substantive consent model that requires information disclosure, patient understanding, free will, and authentic ridā. This reconstruction strengthens patient legal protection, balances therapeutic relationships, and unifies legal certainty with values of justice and ethics in healthcare. Persetujuan medis (persetujuan yang terinformasi) merupakan mekanisme fundamental dalam menjamin otonomi pasien dan perlindungan hukum dalam layanan kesehatan. Meskipun diatur secara komprehensif dalam hukum kesehatan Indonesia, praktik persetujuan yang terinformasi masih cenderung bersifat prosedural dan administratif, sehingga gagal sepenuhnya menjamin kesediaan dan pemahaman substantif pasien. Kondisi ini mengindikasikan ketidakseimbangan struktural dalam hubungan dokter-pasien yang berpotensi melemahkan posisi hukum pasien. Penelitian ini bertujuan untuk menganalisis kelemahan konseptual persetujuan terinformasi dalam hukum positif Indonesia dan merekonstruksinya melalui integrasi prinsip at-tarāḍī dalam hukum kontrak Islam. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual, doktrinal, dan komparatif normatif, melalui analisis peraturan kesehatan, doktrin hukum, dan prinsip-prinsip fiqh muʿāmalāt. Hasil penelitian menunjukkan bahwa regulasi persetujuan terinformasi dalam peraturan nasional lebih menekankan pada pemenuhan formalitas persetujuan daripada kualitas substansial kesediaan dan kehendak bebas pasien. Dengan merekonseptualisasikan persetujuan yang terinformasi sebagai kontrak layanan medis berdasarkan prinsip at-tarāḍī, studi ini mengusulkan model persetujuan substantif yang menuntut pengungkapan informasi, pemahaman pasien, kehendak bebas, dan ridā yang autentik. Rekonstruksi ini berkontribusi memperkuat perlindungan hukum pasien, menyeimbangkan hubungan terapeutik, dan menyatukan kepastian hukum dengan nilai-nilai keadilan dan etika dalam pelayanan kesehatan.